Optimal tuning of 3 degree-of-freedom proportional-integral-derivative controller for hybrid distributed power system using dragonfly algorithm. (November 2018) - Guha, Dipayan; Roy, Provas Kumar; Banerjee, Subrate
Highlights: This paper model and discuss the performance of a hybrid energy distributed power system (HEDPS) coordinated with reheat thermal power plant. Dragonfly algorithm optimized 3DOF-PID controller is proposed to improve the frequency and power profiles of the modeled HEDPS. Results obtained using Dragonfly algorithm is compared with classical and some recently published evolutionary algorithms. Time varying step load perturbation, random wind perturbation, and parameter variations are considered to confirm feasibility and superiority of the designed controller. Probability density function and statistical results are shown to validate the robustness of the proposed method. Abstract: The objective of this paper is to study the dynamic stability of a hybrid energy distributed power system (HEDPS) subject to load and wind power variations. A three degree-of-freedom (3-DOF) proportional-integral-derivative (PID) controller is designed and implemented in the HEDPS to stabilize frequency and power fluctuations after the perturbation. For enhancing system dynamics, the parameters of the 3-DOF PID controller are optimized by using dragonfly algorithm (DA). The results are compared with the results obtained by Zeigler–Nichols tuning and some other well-known meta-heuristic algorithms. The efficacy of proposed DA over different reported algorithms is established in terms of convergence rate, minimum fitness value and dynamic performance of the system. The robustness of the 3-DOF PID-controller is ascertained with time-varying step load perturbation, random wind power perturbation, and under system parameter variation. The robust performance of proposed DA has also been established by performing statistical analysis.